Impact of Insecticide Seed Treatments on Population Dynamics of Euschistus Heros (Fabr.) (Hemiptera: Pentatomidae) - Rodrigues, Thiago Ferreira; Silva, Luciana Barboza; Rodrigues, Raimundo Henrique Ferreira; Almeida, Lorrana Francisca Oliveira; e Silva, Maria Carolina Farias; Pavan, Bruno Ettore [UNESP]; Alvares, Ciro Humberto Almeida; Brito, João Derckson Borges (Pensoft Publishers, 2021)
This study evaluated the effect of insecticides used in the treatment of soybean [(Glycine max (L.) Merrill)] seeds on the population dynamics of Euschistus heros (Fabr.) (Hemiptera: Pentatomidae), popularly known as the Neotropical brown stink bug. The experiment was conducted on 2015/2016 and 2016/2017 soybean crops in the experimental area of the Celeiro Seed Farm. Soybean seeds of the cultivar ‘TMG 132RR®’ were treated with the insecticides imidacloprid + thiodicarb, abamectin, fipronil and chlorantraniliprole. Two controls were used, the conventional cultivar ‘TMG 132RR®’ and the transgenic cultivar ‘M 8644IPRO®’, both without insecticide treatments. Crop I (2015/2016) had an IAD (insects accumulated daily) 2.9 times greater than Crop II (2016/2017); however, treatment with insecticides did not affect the IAD. For Crop I, there was a population peak of E. heros at R5.5 (from 75 to 100% of the full grains), since the soybean treatment with imidacloprid + thiodicarb had 2 and 2.5 times more insects than the conventional and transgenic controls, respectively. For Crop II, there was no population peak of E. heros. The IAD showed significant negative correlations, by F test, with mass of 1,000 seeds - MTS (-0.44112 **) and productivity (-0.45895 **). After analyzing the results, it was verified that there was no residual effect of the insecticides on the population dynamics of E. heros during the cycles and under the conditions of the soybean crops studied.
Keywords: Chemical control; Glycine max; Neotropical brown stink bug